The relationship between subjective knee function and psychological readiness to return to sport after ACL injury: A cross-sectional study - Yuliana, Ela; Purba, Ruliando Hasea; Migrha, Bazzar Ari; Oktafiranda, Nadya Dwi; Nurhidayah, Dewi (UIR Press, 2025)
Background: Athletes with anterior cruciate ligament (ACL) injuries often reduce or stop sports participation due to fear of re-injury and low confidence in their injured knee. While most studies emphasize physical recovery, fewer explore how subjective knee function affects psychological readiness to return to sport. Objectives: This study aims to determine the contribution of self-reported knee symptoms and function (subjective assessment) to psychological readiness to return to sport after ACL injury with operative and non-operative treatment. Methods: This cross-sectional study involved 40 participants who met the inclusion criteria for post-ACL injury, both operative and non-operative. Data were collected using the International Knee Documentation Committee (IKDC 2000) questionnaire for subjective knee function and the Anterior Cruciate Ligament–Return to Sport after Injury (ACL-RSI) scale for psychological readiness. A simple linear regression test was conducted with a 95% confidence interval. Finding/Results: The mean IKDC score was 69.80 ± 12.53 and the mean ACL-RSI score was 58.43 ± 19.12. The regression analysis showed a significant positive relationship between subjective knee function and psychological readiness to return to sport (r = 0.61, p < 0.05), with a coefficient of determination (R2) of 0.373. Conclusion: Subjective knee function significantly influences psychological readiness to return to sport after an ACL injury. Enhancing knee function through targeted rehabilitation programs may improve athletes’ confidence and reduce fear of re-injury, facilitating a safer and more effective return to sport.